Association between depression and suicidal ideation among people living with HIV - Gautam, Anuradha; Mishra, Chandra Mauli (International Journal Of Community Medicine And Public Health, 2022)
Background: Psychological illnesses among PLHIV may cause poor engagement to their HIV care and it may lead to poor treatment outcomes. Therefore, early detection of depression and suicidal behaviour is important for timely intervention to improve mental health and HIV/AIDS-related treatment outcomes. So, the AIM of the study was to assess the prevalence of depression and its relation with suicidal ideation among PLHIV. Methods: This was a cross-sectional and facility-based study, 205 PLHIV were recruited by using systematic random sampling from ART plus centre, Lucknow. Depression and suicidal ideation were assessed using the nine-item patient health questionnaire (PHQ-9) tool. Data were analysed using Chi-square test and multivariate logistic regression in SPSS version-23. Results: The results revealed that the prevalence of depression among study participants was 36.6%, in which about more than half (56.0%) were females and about 54.4% females had suicidal ideation. In the multivariate logistic analysis, gender; AOR=3.07, 95% CI (1.53-6.14), category; AOR=3.66, 95% CI (1.60-8.34), type of family; AOR=0.26, 95% CI (0.12-0.58), socio-economic status; AOR=7.93, 95% CI (2.32-27.06) and PLHIV on co-trimoxazole prophylactic treatment; AOR=0.47, 95% CI (0.23-0.99) were significantly associated with depression Conclusions: The results signify the psychological morbidities of illness among PLHIV, so without good mental health care, people with HIV may fail their treatment, which also affects their health.